Chemical contaminants in Chinese aquaculture imports, U.S. import security, and exposure assessment amongst vulnerable sub-populations - Nyambok, Edward Otieno (Kansas State University, 2011)
Many Chinese aquaculture farmers use unapproved chemicals to treat their fish, many of which are diseased as a result of the country’s poor waste management and environmental practices. During 2006-2007, the United States (U.S.), the European Union, and Japan rejected large amounts of Chinese seafood imports due to the presence of unapproved chemicals or the presence of approved chemicals at concentrations that exceeded permitted levels. This dissertation examines the sources of environmental health and food safety problems in China; it also examines how effective the U.S. and Chinese governments’ regulations are in protecting consumers from hazards in Chinese aquaculture products. The study looks at specific chemical contaminants found in Chinese aquaculture imports, explores their potential toxicity or carcinogenicity, and examines the reasons for their prohibition from human food. The study exploits the available U.S. seafood consumption patterns (courtesy of the National Health and Nutrition Examination Survey—NHANES—database) and then uses probabilistic modeling (courtesy of CREMe Software Limited) to determine the extent to which specific sensitive U.S. consumer subpopulations were exposed to aquaculture chemical contaminants in the food supply in a contrived scenario using real consumption data (from NHANES) and actual contamination data (from the FDA). The study compares exposure between children and adult consumers, and also looks at exposure among women aged 18 years and older and the elderly aged 60 years and older. This study suggests a strong likelihood that NHANES children, as well as female consumers aged 18 years and older and elderly consumers aged 60 years and older, were (in the contrived scenario) all exposed to violative intake levels of chemical contaminants from Chinese aquaculture imports. Children forming the 99.5th and 99.9th percentiles of NHANES seafood consumers were exposed to higher levels of nitrofuran, gentian violet, and malachite green contaminants per kilogram of body weight than were their adult counterparts. Conversely, children were exposed to lower levels of fluoroquinolone contaminants per kilogram of body weight than were their adult counterparts. The 50th, 95th, and 99.9th percentiles of female consumers aged 18 and older and elderly consumers aged 60 years and older were exposed to violative daily intake levels of contaminants in Chinese aquaculture. The study concludes by examining what the U.S. and Chinese governments should do to address aquaculture safety.
Keywords: Food safety; Chinese aquaculture; Chemical contaminants; Exposure assessment; Import security; Vulnerable sub-populations; Public health; Environmental Health (0470); Food Science (0359); Public Health (0573)